Cold cold heart - Hoag, Tami (Dutton, 2015)
Struggling with PTSD a year after escaping a serial killer, television reporter Dana Nolan uses her investigative skills to reclaim the missing pieces of her life and take another look at the case of her best friend's disappearance after high school graduation.